Identification of Cyprodinil + Fludioxonil to Manage Soybean Red Crown Rot Using the Microplate-Based High-Throughput Screening and Pot Assay - Wu, Ping-Hu (Plant disease, 2023)
Red crown rot (RCR), caused by the soilborne fungus Calonectria ilicicola, is an emerging soybean disease in Taiwan, and fungicide screening is desired to identify effective management for C. ilicicola. This study screened 11 fungicides, including azoxystrobin, boscalid, cyprodinil, cyprodinil + fludioxonil, difenoconazole, fluopyram, flutolanil, mancozeb, prochloraz, pyraclostrobin, and tebuconazole, for their inhibitory effects on the mycelial growth of 10 C. ilicicola field isolates. Subsequently, a microplate-based high-throughput screening (MHTS) method was established to measure the fungicide sensitivity in a population composed of 80 C. ilicicola isolates to three effective fungicides, cyprodinil + fludioxonil, fluopyram, and tebuconazole. The MHTS was optimized for multiple factors, including the optical scanning pattern, absorption wavelength, conidial concentration, and measurement timing based on the quality controls of Z' factor and the log-phase growth curve. The population mean EC50 estimated by MHTS were 0.14, 2.34, and 2.46 ppm to cyprodinil + fludioxonil, fluopyram, and tebuconazole, respectively. In addition to the in vitro assessment, fungicide efficacy was evaluated by coating cyprodinil + fludioxonil, fluopyram, or tebuconazole on soybean seeds in the pot assay. The results showed that cyprodinil + fludioxonil significantly reduced both postemergence damping-off and disease severity, while fluopyram and tebuconazole reduced only the postemergence damping-off but not disease severity. Based on the MHTS and the pot assay results, this study demonstrated cyprodinil + fludioxonil to be a potential fungicide to manage soybean RCR